A RandomizEd trial of ENtERal Glutamine to minimIZE thermal injury (The RE-ENERGIZE Trial): a clinical trial protocol - Daren K. Heyland; Paul Wischmeyer; Marc G. Jeschke; Lucy Wibbenmeyer; Alexis F. Turgeon; Henry T. Stelfox; Andrew G. Day; Dominique Garrel (SAGE Publishing, 2017)
Background: Burn injury represents a significant public health problem worldwide. More than in any other injury, the inflammation and catabolism associated with severe burns can exacerbate nutrient deficiencies resulting in impaired immune function and increased risk of developing infection, organ dysfunction and death. Consequently, over the last few decades numerous trials have evaluated the impact of different nutritional strategies in severe burn injury. Glutamine is of particular interest, as it appears vital for a number of key stress-response pathways in serious illness. The purpose of the current manuscript is to provide the rationale and protocol for a large clinical trial of supplemental enteral glutamine in 2700 severe burn-injured patients. Methods: We propose a multicentre, double-blind, pragmatic, randomized, clinical trial involving 80 tertiary intensive care unit (ICU) burn centres worldwide. We aim to enrol patients with deep second- and/or third-degree burns at moderate or high risk for death. We will exclude patients admitted > 72 h before screening and patients with advanced liver and kidney disease. The study intervention consists of enteral glutamine 0.5 g/kg/day vs. isocaloric maltodextran control delivered enterally. Primary outcome will be six-month mortality. Key secondary outcomes include time to discharge alive from hospital, ICU and hospital mortality, length of stay and health-related quality of life at six months. Significance: This study will be the first large international multicentre trial examining the effects of glutamine in burn patients. Negative or positive, the results of this trial will inform the clinical practice of burns care worldwide. Clinicaltrials.gov ID #NCT00985205